Genetic Diversity Analysis of Leaf Blight Resistant and Susceptible Taro [Colocasia esculenta (L.) Schott] Genotypes Using ISSR Markers - U. M., Anjitha Nair; A., Asha Devi; S. S., Veena; B. S., Prakash Krishnan; R. S., Arya (JOURNAL OF ROOT CROPS, 2020)
Taro is believed to have originated in the Indo-Malayan region and hence harbors a wide genetic diversity. The major problem associated with taro cultivation is taro leaf blight (TLB) caused by Phytophthora colocasiae. Germplasm of taro maintained at ICAR-CTCRI was continuously screened for resistance for the last four years and as a result, few resistant genotypes were identified. An attempt was made here to assess the genetic diversity existing in this set along with susceptible genotypes present in the germplasm collection using ISSR. Thirty six genotypes of C. esculenta from different parts of India including five varieties were used in the study. The genotypes used were classified as resistant and susceptible based on their reactions to TLB, previous studies. Fourteen ISSR markers were used on 18 resistant and 18 susceptible taro genotypes. The primers selected were suitable for the study as reflected by the mean percentage polymorphism of 95.7%, heterozygosity ranging from 0.75-0.87, average number of alleles ranging between 1.94-6.13 and Polymorphic Information Content (PIC) ranging from 0.71-0.86. Similarity matrix based on Jaccard’s coefficient ranged from 0.50 to 0.88 and the genotypes were grouped into two major clusters. The clusters were sub-divided into four and three sub-clusters, respectively along with an outlier. Cluster I comprised of 12 resistant and seven susceptible lines whereas Cluster II had eight resistant and nine susceptible genotypes grouped together. Of the seven sub-clusters, resistant genotypes were grouped together in three sub-clusters viz., 1a, 1b and 2a. The sub-cluster 2d had only susceptible genotypes pooled together. In the rest three sub-clusters viz., 1c, 1d and 2b resistant and susceptible genotypes grouped together. In sub cluster Id, of the eight genotypes grouped together, only one was resistant, IC012470 which pooled with Sree Rashmi in the dendrogram at 88% similarity. Phenotypically the genotype IC012470 caught mild infection. This work shows that ISSR is able to assess the genetic diversity present among taro genotypes and also helped to group the taro genotypes on the basis of TLB resistance/susceptibility to a large extent. Few genetically divergent genotypes could be identified, viz., IC012593 in 1a, TCR 429 in 1b, C-565 in 1c, B4 in 2a, C-679 in 2b as well as IC089583 and B2(SVP) in 2c. The divergent genotypes identified were resistant to TLB except B2(SVP), which was susceptible. The TLB resistant genetically divergent genotypes can be used as diverse parents for development of a mapping population for TLB resistance along with susceptible sources and also for introgression of resistance to popular high yielding varieties which are susceptible to TLB.